Protective Effects of Korean Herbal Remedy against Airway Inflammation in an Allergic Asthma by Suppressing Eosinophil Recruitment and Infiltration in Lung - Soyon Yoon; Seokcheon Song; Jae Woo Shin; Sini Kang; Hye Young Kim; Hyun Ju You (MDPI AG, 2020)
The increasing prevalence of allergic asthma has become the world's major health issue. Current treatments for allergic asthma focus on treating symptoms, while permanent cures still remain undiscovered. In this study, we investigated the effect of Korean traditional herbal remedy, Pyunkang-tang (PGT)-composed of six plants-on asthma alleviation in a mouse model. The PGT mixture was orally gavaged to mice (PM group, 20 mg/mouse/day) from 7 days before sensitization with ovalbumin (OVA) (day −7). On day 0 and day 14, mice from OVA-control (n = 9) and PM group (n = 8) were sensitized with OVA and alum through intraperitoneal injection. On days 18~20, OVA was challenged to mice through nasal injection and sacrificed next day. Cell profile in lung tissue was analyzed by flow cytometry and RT-qPCR analysis, and the number of eosinophils and expression of siglec-F were significantly reduced in the PM group. Lung tissue was examined with hematoxylin and eosin (H&E) and Alcian blue/periodic acid-Schiff (AB-PAS) staining. Noticeably reduced eosinophil infiltration around bronchioles was displayed in the PM group compared to the OVA-control group. Furthermore, PGT-treated mice showed a significant reduction in IL-13 and a mild reduction in IL-5 in lungs. A decreasing tendency of IL-5/13 (+) CD4+ T cells and IL-13(+) innate lymphoid cells (ILCs) and a significant reduction in IL5(+) ILCs were also observed. When treating PGT on murine lung epithelial cells stimulated by papain, there was a significant reduction in IL-33 mRNA expression levels. Taken together, oral delivery of PGT successfully alleviated asthmatic responses provoked by OVA in a mouse model and could lead to novel therapies for allergic asthma.